2019
DOI: 10.1186/s13046-019-1176-1
|View full text |Cite
|
Sign up to set email alerts
|

Activity and molecular targets of pioglitazone via blockade of proliferation, invasiveness and bioenergetics in human NSCLC

Abstract: Background: Pioglitazone, a synthetic peroxisome proliferator activated receptor (PPAR-γ) ligand, is known as an antidiabetic drug included in the thiazolidinediones (TZDs) class. It regulates the lipid and glucose cell metabolism and recently a role in the inhibition of numerous cancer cell processes has been described. Methods: In our work we investigate the anti-tumor effects of pioglitazone in in vitro models of non small cell lung cancer (NSCLC) and also, we generated ex-vivo three-dimensional (3D) cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
(31 reference statements)
3
26
0
Order By: Relevance
“…So GCNT2 may be a novel gene contributing to metastasis with preferential expression in lung cancer, implying that blocking the TGFβ/GCNT2 signal pathway is a promising approach for targeting metastatic NSCLC. Furthermore, we found that APEX1 can activate the TGFβ/SAMD3 signal pathway by promoting lung cancer cells proliferation, as described previously [50]. For the TGFβ/SMAD3 signaling pathway, receptor-activated SAMD complexes activate or repress their target gene promoters.…”
Section: Validation Of Apex1-regulated Gene Expression and Alternativsupporting
confidence: 86%
“…So GCNT2 may be a novel gene contributing to metastasis with preferential expression in lung cancer, implying that blocking the TGFβ/GCNT2 signal pathway is a promising approach for targeting metastatic NSCLC. Furthermore, we found that APEX1 can activate the TGFβ/SAMD3 signal pathway by promoting lung cancer cells proliferation, as described previously [50]. For the TGFβ/SMAD3 signaling pathway, receptor-activated SAMD complexes activate or repress their target gene promoters.…”
Section: Validation Of Apex1-regulated Gene Expression and Alternativsupporting
confidence: 86%
“…TZD18, a dual PPARγ/α ligand, reduced the growth and increased the apoptosis of human gastric cancer cells by increasing the expression of BAX and p27kip1 and decreasing Bcl-2 (Ma et al, 2019). Similar activity was observed for renal carcinoma cells (Wu et al, 2019), cutaneous squamous cell carcinoma cells (Wolff et al, 2019), non-small cell lung carcinoma (Liu and Fang, 1983; Ciaramella et al, 2019) and prostate cancer cells (Masure et al, 1983). Ciaramella et al (2019) also correlated the anti-cancer activity of PPARγ to its effects on cancer microenvironment bioenergetics and metabolism.…”
Section: Potential Effect Of Pparγ Agonists On Cancersupporting
confidence: 59%
“…During the progression of EMT, the expression of epithelial markers such as E-cadherin was usually downregulated, while the expression of mesenchymal markers such as N-cadherin and vimentin was upregulated [23]. Previous studies have reported that pioglitazone restrained the proliferation and invasion of NSCLC cells via downregulating TGF-β to weaken EMT, and DEHP activated EMT via Wnt/β-catenin signal transduction pathway to promote the progress of NSCLC [24,25]. Such studies indicates that EMT is a crucial mechanism for the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%